Theology and Mathematics in Plato’s Later Ethics - Bartninkas, Vilius (Literatūra, 2022)
In Plato’s later ethics, the key challenge to one’s personal progress is unorderly thoughts and motions of soul. This disorder should be corrected by recognising and repeating the orderly thoughts and motions of cosmic gods. This paper examines the theoretical assumptions of Plato’s later ethics. A closer analysis of the Timaeus reveals a peculiar conception of mathematics, according to which numbers and their relations not only reveal facts about the reality, but also express values and ideals. By learning mathematics human beings come to know the everyday ethical life of cosmic gods and become like them.
Keywords: Plato; Timaeus; mathematics; theology; cosmic gods